Novel high-sensitivity cardiac troponin I assay in patients with suspected acute coronary syndrome. Issue 8 (15th November 2018) - Chapman, Andrew R; Fujisawa, Takeshi; Lee, Kuan Ken; Andrews, Jack Patrick; Anand, Atul; Sandeman, Dennis; Ferry, Amy V; Stewart, Stacey; Marshall, Lucy; Strachan, Fiona E; Gray, Alasdair; Newby, David E; et al.
Abstract : Background: High-sensitivity cardiac troponin assays enable the early risk stratification of patients with suspected acute coronary syndrome to identify those at low risk of myocardial infarction or cardiac death. We evaluated the performance of a novel high-sensitivity cardiac troponin I assay in early rule out pathways. Methods: In 1920 patients with suspected acute coronary syndrome, cardiac troponin was measured using the Siemens Atellica high-sensitivity cardiac troponin I assay (99th centile: 34 ng/L women, 53 ng/L men). We evaluated three pathways which use either low risk-stratification thresholds of cardiac troponin ( High-S ensitivity T roponin in the E valuation of patients with A cute C oronary S yndrome (High-STEACS) and the European Society of Cardiology (ESC) 1 hour pathway) or the 99th centile diagnostic threshold (ESC 3 hour pathway) to rule out myocardial infarction. Results: The primary outcome of myocardial infarction or cardiac death at 30 days occurred in 14.4% (277/1920). The High-STEACS pathway ruled out 63% of patients (1218/1920), with five missed events for a negative predictive value (NPV) of 99.5% (95% CI (CI) 99.1% to 99.8%). Similar performance was observed for the ESC 1 hour pathway with an NPV of 99.0% (97.6% to 99.8%). In contrast, the ESC 3 hour pathway ruled out 65% of patients (1248/1920), but missed 25 events for an NPV of 98.0% (97.1% to 98.7%). Conclusions: A novel high-sensitivity cardiac troponin I assay can safely identify patients at low risk of myocardial infarction or cardiac death. Diagnostic pathways that use low cardiac troponin concentrations for risk stratification miss fewer events than those that rely on the 99th centile to rule out myocardial infarction. Trial registration: NCT1852123 .